THE ROLE OF PURCHASE DECISIONS IN MEDIATING THE EFFECT OF RESPONSIBILITY AND PERSONALIZATION IN CHATBOTS ON CUSTOMER SATISFACTION OF FASHION PRODUCTS AT TIKTOK SHOP IN PALU CITY - Syarifaini; Ira Nuriya Santi; Maskuri Sutomo; Mohammad Zeylo Auriza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the role of purchasing decisions as a mediator of the influence of chatbot responsiveness and personalization on customer satisfaction on TikTok Shop in Palu City. Using quantitative methods with SEM-PLS (SmartPLS 4) and purposive sampling techniques, the study involved 100 respondents who had interacted with a chatbot when purchasing fashion products on TikTok Shop. The results show that responsiveness and personalization do not directly influence satisfaction, but both have a significant influence on purchasing decisions. Subsequent purchasing decisions are proven to have a strong influence on satisfaction and act as a full mediator. These findings reflect field conditions, where TikTok Shop users value chatbots more from their ability to assist the decision-making process such as clarity of information, relevant recommendations, and ease of transactions than from the emotional aspect of direct satisfaction. Practically, TikTok Shop needs to optimize the quality of chatbot responses, enrich personalization based on shopping history, and improve the accuracy of product information to encourage purchasing confidence, which ultimately increases customer satisfaction.